2022
DOI: 10.1186/s12891-022-06076-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on the accuracy of DXA BMD for DXA-equivalent BMD estimation

Abstract: Introduction As the radiomics technique using texture features in CT is adopted for accessing DXA-equivalent bone mineral density (BMD), this study aims to compare BMD by DXA and predicted BMD to investigate the impact of obesity and central obesity in general patients. Materials and methods A total of 710 cases (621 patients) obtained from May 6, 2012, to June 30, 2021, were used in the study. We focused both their abdomen & pelvis CT’s first … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Interestingly, our study also revealed discordance between the CT and DXA measurements in certain scenarios. This discordance could stem from various factors, including differences in the measured regions, methodological discrepancies, or inherent inaccuracies in DXA scanning, particularly in patients with degenerative changes or abdominal obesity [ 10 ]. DXA measurements are known to be susceptible to inaccuracies in individuals with high abdominal fat content due to overlaying soft tissue artifacts [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study also revealed discordance between the CT and DXA measurements in certain scenarios. This discordance could stem from various factors, including differences in the measured regions, methodological discrepancies, or inherent inaccuracies in DXA scanning, particularly in patients with degenerative changes or abdominal obesity [ 10 ]. DXA measurements are known to be susceptible to inaccuracies in individuals with high abdominal fat content due to overlaying soft tissue artifacts [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous intricate pathways exist through which obesity might affect the connection between diabetes and BMD. The influence of body fatness on the precision of DXA-based BMD assessments, as evidenced in obese individuals with diabetes, is noteworthy [ 23 ]. However, the potential measurement error should be of minimal concern, given that this phenomenon has been demonstrated to potentially result in either underestimation or overestimation of values.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies, our investigation is not limited to the L1 region. Instead, we considered a broader range, spanning from T12 to S1, a factor that enhances the robustness of our findings [26,27]. We chose to employ spine CT scans for this texture analysis due to their frequent usage during health checkups, often alongside DXA scans for osteoporosis diagnosis.…”
Section: Discussionmentioning
confidence: 99%